Analisis Yuridis Pelayanan Radiologi Klinik terhadap Dokter Gigi dan Pasien - Rio Faisal Ariady; Asmuni Asmuni (Faculty of Law Hang Tuah University, 2022)
Juridically analyze the regulations governing the services of Clinical Radiology for Dentists and Patients. The purpose of this research is to look at the aspects of Norms Conflict, Legal Responsibilities, and also legal protection for related legal subjects. The research method used is normative law, namely document studies with a statutory approach and a conceptual approach. This research aims to determine the norms in the Regulation of the Minister of Health which regulates related to Radiology Services are contrary to the norms in the laws and regulations that regulate the competence of a dentist as well as those that regulate the rights of patients. The use of principle of legal conflict lex superior derogate legi Inferiore is used because the regulation of the authority of dentists has been explicitly regulated in the Act where the hierarchy in the legislation has a higher position than the Regulation of the Minister of Health. So that the dentist in terms of responsibility for clinical radiology services still adheres to the law that regulates the competence of dentists. In terms of protecting dentists or patients, it can be taken through preventive and repressive legal protection.